Beyond containment: driving change in residential care: a Queensland, Australia model of therapeutic residential care - Shelley Wall; Stewart Redshaw; Kym Edwards (Scottish Journal of Residential Child Care)
Mercy Family Services is a Non-Government Organisation providing a range of out of home care services, including one 'therapeutic residential' and 12 traditional residential care programmes across South East Queensland, Australia. This paper will examine the implementation of a model of therapeutic residential care developed to address a gap in service delivery identified in the Crime and Misconduct Commission: An Inquiry Into Abuse In Foster Care in January 2004, which found there was a need for more therapeutic treatment programmes in order to assist children and young people with severe psychological and behavioural problems (Crime and Misconduct Commission, 2004).